Review of therapeutic mechanisms and applications based on SARS-CoV-2 neutralizing antibodies - Liu, Mingtao; Gan, Hui; Liang, Zhiman; Liu, Li; Liu, Qiwen; Mai, Yiyin; Chen, Huihuang; Lei, Baoying; Yu, Shangwei; Chen, Huihui; Zheng, Peiyan; Sun, Baoqing (Frontiers in Microbiology, 2023)
COVID-19 pandemic is a global public health emergency. Despite extensive research, there are still few effective treatment options available today. Neutralizing-antibody-based treatments offer a broad range of applications, including the prevention and treatment of acute infectious diseases. Hundreds of SARS-CoV-2 neutralizing antibody studies are currently underway around the world, with some already in clinical applications. The development of SARS-CoV-2 neutralizing antibody opens up a new therapeutic option for COVID-19. We intend to review our current knowledge about antibodies targeting various regions (i.e. RBD regions, non-RBD regions, host cell targets, and cross-neutralizing antibodies), as well as the current scientific evidence for neutralizing-antibody-based treatments based on convalescent plasma therapy, intravenous immunoglobulin, monoclonal antibodies, and recombinant drugs. The functional evaluation of antibodies (i.e. in vitro or in vivo assays) is also discussed. Finally, some current issues in the field of neutralizing-antibody-based therapies are highlighted.